2018
DOI: 10.1111/dsji.12167
|View full text |Cite
|
Sign up to set email alerts
|

5S Your Life: Using an Experiential Approach to Teaching Lean Philosophy

Abstract: Within the Information Systems domain, employers are often dissatisfied with graduates’ competence of the necessary technical skills in the area of integrated business processes. However, teaching complex concepts related to integrated business processes—such as the 5S lean philosophy—is particularly challenging. In this article, we describe how Kolb's experiential learning cycle was used to design a direct‐experience project to support students’ learning of the 5S lean philosophy. We also share the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This effect can be attributed to the nature of the training’s teaching methods used, for example, on-site exercises with active learning activities that provide greater interaction with study objects, as observed in Goldberg and Rank (2013), Mamat et al (2015); and Ahmad et al (2018). In addition, according to Netland et al (2012), Witt et al (2018); and Abdi et al (2018), organisations that actively implement LM by fostering knowledge management practices are more likely to have their work habits changed as LM practices are integrated into the work routine, contributing to the establishment of a learning environment across the company.…”
Section: Resultsmentioning
confidence: 99%
“…This effect can be attributed to the nature of the training’s teaching methods used, for example, on-site exercises with active learning activities that provide greater interaction with study objects, as observed in Goldberg and Rank (2013), Mamat et al (2015); and Ahmad et al (2018). In addition, according to Netland et al (2012), Witt et al (2018); and Abdi et al (2018), organisations that actively implement LM by fostering knowledge management practices are more likely to have their work habits changed as LM practices are integrated into the work routine, contributing to the establishment of a learning environment across the company.…”
Section: Resultsmentioning
confidence: 99%